Character Values in Ahmad Fuadi's Novel Buya Hamka as a Source for Learning History - Pamungkas, Sephia Nara Putri; Meihan, Andre Mustofa (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to analyze the character values contained in the novel